ATR-Mediated FANCI Phosphorylation Regulates Both Ubiquitination and Deubiquitination of FANCD2 - Tan, Winnie; van Twest, Sylvie; Murphy, Vincent J.; Deans, Andrew J. (Frontiers in Cell and Developmental Biology, 2020)
DNA interstrand crosslinks are a physical barrier to replication and therefore toxic to cell viability. An important mechanism for the removal of interstrand crosslinks is the Fanconi Anemia DNA repair pathway, which is initiated by mono-ubiquitination of FANCD2 and its partner protein FANCI. Here, we show that maintenance of FANCD2 and FANCI proteins in a monoubiquitinated form is regulated by the ATR-kinase. Using recombinant proteins in biochemical reconstitution experiments we show that ATR directly phosphorylates FANCI on serine 556, 559 and 565. This phosphorylation stimulates the conjugation of ubiquitin to both FANCI and FANCD2, but also inhibits ubiquitin deconjugation. Using phosphomimetic and phosphodead mutants of FANCI we show that S559 and S565 are particularly important for protecting the complex from the activity of the deubiquitinating enzyme USP1:UAF1. Our results reveal a major mechanism by which ATR kinase maintains the activation of the FA pathway, by promoting the accumulation of FANCD2 in the ubiquitinated form active in DNA repair.